Effectiveness Of Cassia alata L Leaf Extract Decrease Blood Glucose Level On Streptozotocin-Induced Male White Rats - Niluh Puspita Dewi; Febry Grasela Aula; Indah Kurnia Utami; Ayu Wulandari; Rezky Yanuarty; Wayan Wirawan (Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction: Diabetes mellitus (DM) is a condition in which the body either fails to produce enough insulin at the right time or fails to use it properly. Aims: The goal of this study is to show how Cassia alata L. leaf extract affects blood glucose levels in streptozotocin-induced diabetic rats. Methods: Cassia alata L. leaves therapy is an alternative treatment for DM. In this investigation, laboratory techniques were employed. Streptozotocin was administered intraperitoneally to mice at a dose of 40 mg/kg body weight initially. Except that they produce normal controls. Six groups of 30 rats each received treatment with Cassia alata L. leaf extract at doses of 500 mg/kg body weight, 600 mg/kg body weight, and 700 mg/kg body weight in addition to the usual control group. Trial outcome data were first examined using one-way ANOVA to confirm differences between treatments and then put through the DUNCAN trial. Result: As a result, it was discovered that secondary metabolites of alkaloids, flavonoids, saponins, and tannins were present in the ethanol extract of Cassia alata L. leaves. A dose of 700 mg/kg body weight is an effective blood sugar-lowering dose, with an average reduction of 121 mg/dl. Conclusion: Ethanol extract from Cassia alata L. leaves has this effect.